SIRT3 in Neural Stem Cells Attenuates Microglia Activation-Induced Oxidative Stress Injury Through Mitochondrial Pathway - Jiang, De-Qi; Wang, Yan; Li, Ming-Xing; Ma, Yan-Jiao; Wang, Yong (Frontiers in Cellular Neuroscience, 2017)
Sirtuin 3 (SIRT3), a mitochondrial protein, is involved in energy metabolism, cell apoptosis and mitochondrial function. However, the role of SIRT3 in neural stem cells (NSCs) remains unknown. In previous studies, we found that microglia activation-induced cytotoxicity negatively regulated survival of NSCs, along with mitochondrial dysfunction. The aim of this study was to investigate the potential neuroprotective effects of SIRT3 on the microglia activation-induced oxidative stress injury in NSCs and its possible mechanisms. In the present study, microglia-NSCs co-culture system was used to demonstrate the crosstalk between both cell types. The cytotoxicity of microglia activation by Aβ resulted in the accumulation of reactive oxygen species (ROS) and down-regulation of SIRT3, manganese superoxide dismutase (MnSOD) gene expression in NSCs, concomitant to cell cycle arrest at G0/G1 phase, increased cell apoptosis rate and opening of the mitochondrial permeability transition pore (mPTP), and enhanced mitochondrial membrane potential (ΔΨm) depolarization. Furthermore, SIRT3 knockdown in NSCs via siRNA accelerated cell injury, whereas SIRT3 overexpression provided resistance to microglia activation-induced oxidative stress cellular damage. The mechanisms of SIRT3 attenuated activated microglia-induced NSC dysfunction included the decreased mPTP opening and cyclophilin D (CypD) protein expression, inhibition of mitochondrial cytochrome C (Cyt C) release to cytoplasm, declined Bax/Bcl-2 ratio, and reduced caspase-3/9 activity. Taken together, these data imply that SIRT3 ameliorates microglia activation-induced oxidative stress injury through mitochondrial apoptosis pathway in NSCs, these results may provide a novel intervention target for NSC survival.